Metabolomic profiling of brassinolide and abscisic acid in response to high-temperature stress - Lv, Jinhua; Dong, Tianyu; Zhang, Yanping; Ku, Yu; Zheng, Ting; Jia, Haifeng; Fang, Jinggui (Plant cell reports, 2022)
Key message Hormone treatment enhanced the content of osmotic substances under high-temperature conditions. The effect of ABA and BR treated separately is better than treated together. To determine the effect of abscisic acid (ABA), brassinolide (BR) and ABA + BR on grape quality under high-temperature stress, various metabolites were analyzed. Compared with the control (CK), DL-tryptophan, d -raffinose, geniposidic acid, dodecanedioic acid and polyphenols were found to be higher after ABA treatment. After BR treatment, amino acids and poricoic acid B were higher than in CK. And carbohydrates and amino acids were up-regulated after ABA + BR treatment. BR and ABA + BR treatment also induced higher endogenous ABA and epibrassinolide contents. In addition, treated grape had higher soluble solid concentrations and soluble sugar content, and delayed the degradation of middle lamella and microfibrils. Antioxidant and heat shock-related genes were examined, which significantly increased in treated grape. The finding of this study suggested that ABA, BR and ABA + BR are very useful for alleviating high-temperature damage by increasing the accumulation of osmotic adjustment substances, and endogenous hormones content.